2022
DOI: 10.1101/2022.03.09.483683
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

NLGC: Network Localized Granger Causality with Application to MEG Directional Functional Connectivity Analysis

Abstract: Identifying the causal relationships that underlie networked activity between different cortical areas is critical for understanding the neural mechanisms behind sensory processing. Granger causality (GC) is widely used for this purpose in functional magnetic resonance imaging analysis, but there the temporal resolution is low, making it difficult to capture the millisecond-scale interactions underlying sensory processing. Magnetoencephalography (MEG) has millisecond resolution, but only provides low-dimension… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 148 publications
(266 reference statements)
0
1
0
Order By: Relevance
“…Structural connectivity is typically extracted from tractography algorithms applied to diffusion magnetic resonance imaging (MRI) or diffusion tensor imaging (DTI) data [4]. Functional connectivity usually refers to pairwise correlation between activation signals in various brain regions is measured by various functional brain imaging modalities - functional MRI (fMRI) [5], electroencephalography (EEG) [6], magnetoencephalography (MEG) [7] etc. Although several studies [8, 9, 10, 11, 12, 13, 14, 15, 16] have suggested that whole brain functional connectivity is shaped by the underlying structure, the rule by which anatomy constraints brain dynamics remains an open question and an interesting research challenge [10].…”
Section: Introductionmentioning
confidence: 99%
“…Structural connectivity is typically extracted from tractography algorithms applied to diffusion magnetic resonance imaging (MRI) or diffusion tensor imaging (DTI) data [4]. Functional connectivity usually refers to pairwise correlation between activation signals in various brain regions is measured by various functional brain imaging modalities - functional MRI (fMRI) [5], electroencephalography (EEG) [6], magnetoencephalography (MEG) [7] etc. Although several studies [8, 9, 10, 11, 12, 13, 14, 15, 16] have suggested that whole brain functional connectivity is shaped by the underlying structure, the rule by which anatomy constraints brain dynamics remains an open question and an interesting research challenge [10].…”
Section: Introductionmentioning
confidence: 99%